On Insider-Outsider in North East India - Amanda Bashisha Basaiawmoit (Space and Culture, India)
In recent years, scholars have increasingly examined the critical questions of identity in North East India, revealing the intricate inter-group relationships essential for understanding human interactions. A significant aspect of this discourse is the phenomenon of ‘othering’, which fosters binaries such as ‘us and them’ and underscores the marginalisation that arises from this process. The complexities of these intergroup dynamics pose vital questions regarding belonging. In the context of North East India, this is manifested in two primary ways. Individuals from this region face marginalisation and are subsequently othered by their fellow citizens in mainland India, who ascribe to them a distinct 'Northeast identity’. Conversely, residents from various states within the region often perceive settlers, particularly those from mainland India, as outsiders or non-natives, thereby reinforcing their own status as insiders.